2006
DOI: 10.1029/2006jd007238
|View full text |Cite
|
Sign up to set email alerts
|

A clear‐sky radiance archive from Meteosat “water vapor” observations

Abstract: A long‐term archive of clear‐sky Meteosat “water vapor” observations, covering the July 1983 to February 1997 period with a 3 hourly time step and a spatial resolution of 0.625°, is presented. Cloud clearing is performed using a scene selection procedure based on the International Satellite Cloud Climatology Project DX product. In this procedure low cloud scenes are kept because of the negligible contribution of the low atmospheric layer in this spectral band. Cloud contamination is shown to have little influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 46 publications
(72 reference statements)
2
36
0
Order By: Relevance
“…It will provide a very good data set to study the variability of water vapor at intraseasonal scale. Brogniez et al (2006) found from a series of Meteosat First Generation data for the period 1983-2005 an asymmetry between the two hemispheres along the annual cycle. Whereas the intra-seasonal variability is homogeneous in the Southern Hemisphere the variability shows a distinct minimum in the Northern Hemisphere during the summer.…”
Section: The Integration Of New Products That Facilitate a Better Undmentioning
confidence: 99%
“…It will provide a very good data set to study the variability of water vapor at intraseasonal scale. Brogniez et al (2006) found from a series of Meteosat First Generation data for the period 1983-2005 an asymmetry between the two hemispheres along the annual cycle. Whereas the intra-seasonal variability is homogeneous in the Southern Hemisphere the variability shows a distinct minimum in the Northern Hemisphere during the summer.…”
Section: The Integration Of New Products That Facilitate a Better Undmentioning
confidence: 99%
“…The elaboration of the Meteosat clear-sky radiance (CSR) archive is described in Brogniez et al (2006), and it is briefly revisited in Sect. 3.…”
Section: Input Datamentioning
confidence: 99%
“…The 6.3 µm BT, sensitive to high-altitude cloud and mid-to upper-tropospheric relative humidity (e.g. Brogniez et al, 2006), highlights the three main convective centres (with BT around 225 K) present in the GERB OLR field. Much of the ocean region to the south of the African coast experienced high BT (around 245 K), symptomatic of a dry, cloud-free upper troposphere.…”
Section: Convectively-generated Cloud Over the Gulf Of Guineamentioning
confidence: 99%